Benign Fibrous Histiocytoma of the Sacrum: A Rare Scenario - Ashish Acharya; Sarvpreet Singh Grewal; B John Paul Sudhakar (Indian Journal of Neurosurgery)
Benign fibrous histiocytoma (BFH) of bone is quite rare, and here we report the second case of such tumor originating from sacrum, with the first being reported in an 18-year-old female. The overlapping clinical, radiological, and histopathological findings make it a difficult diagnosis along with the fact that it is a rare diagnosis. In this case report, we present the diagnostic difficulties and optimal treatment for such cases. A 46-year-old male w presented to OPD with complaint of numbness in left foot since 1 month, and intermittent urinary incontinence for 2 weeks. On examination, the straight leg raising test was positive of left side, extensor hallucis longus (EHL) was weak in both lower limbs, and bilateral ankle jerks were diminished. MRI showed well-defined lobulated solid mass lesion, which is T1 hypointense and T2 hyperintense and homogeneously involving the S1 vertebral body, with involvement of the right sacral ala, and right sacral foramen seen at S1 and S2 levels extending into the spinal canal till L4 level. Excision through a posterior midline incision was performed taking care to preserve the traversing nerves. Postoperatively, remarkable improvement in pain with no major residual neurological deficit was observed. Patient was followed-up till 9 months; patient’s incontinence improved over a period of 3 months and has stayed the same until the last follow-up.